1
$\begingroup$

Having some problems with a determinant of a 4x4 matrix M.

$ M = \left( {\begin{array}{cc} 1 & 2 & 3 &-1 \\ 0 & 1 & 2 & 2 \\ 1 &1 &0 &0 \\ 3&1&2&0 \end{array} } \right) $

Went along and developed it according to the 4th column. So I end up with two matrixes A and B.

$ A = -1 \cdot det \left( {\begin{array}{cc} 0 & 1 & 2 \\ 1 & 1 & 0 \\ 3 &1 &2 \\ \end{array} } \right) $

$ B = 2 \cdot det \left( {\begin{array}{cc} 1 & 2 & 3 \\ 1 & 1 & 0 \\ 3 &1 &2 \\ \end{array} } \right) $

I get $A= (-1) \cdot((0 \cdot1\cdot2)+(1\cdot0\cdot3)+(2\cdot1\cdot1)-(3\cdot1\cdot2)-(1\cdot2\cdot2)-(1\cdot1\cdot0)) \\$

$A=(-1) \cdot(-6)=6$

$B= 2 \cdot((1\cdot1\cdot2)+(2\cdot0\cdot3)+(3\cdot1\cdot1)-(3\cdot1\cdot3)-(1\cdot2\cdot2)-(1\cdot1\cdot0)) \\$

$B = 2\cdot8=16$

$A+B=22$

which is wrong. Where is my mistake? The correct answer should be $-22$ but I don't get why my solution keeps being positive.

Edit: im such a moron: A = 1* det and B = -2 * det. Everythings clearing up while in bed. Hehe!

$\endgroup$
  • 3
    $\begingroup$ You need to alternate the sign with each element, starting with '+' for the top left element. $\endgroup$ – Ataraxia Jun 11 '13 at 18:37
2
$\begingroup$

The formula to calculate the determinant is given by

$$\sum_{\sigma \in S_n} (-1)^{\sigma} a_{1\sigma(1)} \times \cdots \times a_{n \sigma(n)},$$

if you want me to explain the whole formula, I can but the important bit right now is the $(-1)^{\sigma}$ which refers to the sign of each entry you are expanding by.

First, you have expanded by element $a_{1,4}$ and so the sign should be $(-1)^{1 + 4} = -1$ and so your determinant of $A$ should be

$$(-1) \cdot (-1) \cdot (-6) = -6.$$

So, your sign for when expanding by row $4$ column $2$ is going to be $(-1)^6 = 1$.

Another mistake you have made is that the determinant of $B$ isn't $16$, it's $-16$.

$\endgroup$
  • $\begingroup$ Ok, re-reading the question, it's not exactly "determinant of $A$" and "determinant of $B$", but you get what I mean? $\endgroup$ – Kaish Jun 11 '13 at 18:47
1
$\begingroup$

You are expanding down the fourth column, which means that the cofactor on entry $ \ a_{14} = -1 \ $ is negative and the cofactor on entry $ \ a_{24} = 2 \ $ is positive. You should have

$$ [ (-1) \cdot (-1) \cdot ( 2 - 6 - 2 ) ] \ + \ [ (+1) \cdot 2 \cdot ( 2 + 3 - 9 - 4 ) ] $$

$$ = \ (-6) \ + \ (-16) \ = \ -22 \ . $$

$\endgroup$
1
$\begingroup$

Your mistake was that you forgot the $(-1)^{i+j}$ for the cofactors.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.